Analisis Pengaruh Usia Karyawan Terhadap Rata – Rata Jam Kerja Karyawan - Deri Rizky Indra P deri (Jejaring Penelitian dan Pengabdian Masyarakat (JPPM), 2026)
This study aims to analyze the effect of employee age on average daily working hours using a simple linear regression method. In the workplace, employee age is often associated with productivity and work patterns, so it is important to understand whether there is a significant relationship between age and daily working hours. The data used in this study includes employee age as the independent variable (X) and average daily working hours as the dependent variable (Y). In addition, other factors such as sleep duration, exercise time, productivity scores, screen time, and travel time to work were collected to provide additional insights, although they were not the main variables in the regression analysis. A simple linear regression method was used to identify patterns of relationships between age and daily working hours, and to test whether age has a significant effect on working hours. The results of the study indicate a positive/negative/insignificant relationship – adjust according to the analysis results) between age and employee working hours. These findings can provide insights for companies in designing more effective work policies that are appropriate for employee age groups.